كفاءة استاد التربية البدنية وعلاقتها بتخفيض السلوك العدواني لدى التلاميذ المراهقين - بوعروري, جعفر (دفـاتر المـــــــــــخبـر, 2018)
ملخص: تهدف هذه المقالة لدراسة مدى كفاءة أستاذ التربية البدنية والرياضية في تخفيض السلوك العدواني لدى التلاميذ المراهقين، وتتبلور الإشكالية في محاولة الوقوف على مدى كفاءة أستاذ التربية البدنية والرياضية على التحكم في السلوك العدواني للتلاميذ المراهقين، وذلك بفضل ما يمتلكه من معلومات تربوية وقدرة على التصرف الصائب في المواقف التربوية. Abstract: This article is intended to study the efficiency of the professor of physical education and sports in the reduction of aggressive behavior in children adolescents, and crystallize problematic to try to stand on the efficiency of the professor of physical education and sports to control the aggressive behavior of students teens, it’s result of educational information and the ability to act right in Educational situation.